Analisis Kondisi Ekonomi Global Terhadap Pergerakan IDX30 Selama Pandemi Covid 19 - Siti Wardani Bakri Katti (Universitas Merdeka Madiun, 2021)
This study aimed to determine the effect of global economic uncertainty which comprises: world oil price, Federal fund rate, Dow Jones Industrial Average Index and the Rupiah currency partially or simultaneously on the capital market. In this study IDX30 index used as research objects that represent the capital market, as well as to determine the dominant variable affecting IDX30 index. The population in this study all companies included in the IDX30 index members. Samples were taken using saturation sampling, that the whole company is a member IDX30 index used as a sample. Data analysis techniques used in this research is multiple linear regression analysis. The result showed: (1) World oil price do not significantly influence the IDX30 index, (2) Federal fund rate significantly influence IDX30 index, (3) Rupiah currency significant effect on IDX30, (4) Dow Jones Industrial Average index significantly influence IDX30 index, (5) World oil price, Federal fund rate, Dow Jones Industrial Average index and Rupiah currency simultaneously significant effect on the IDX30 index, as well as, (6) the dominant variable affecting IDX30 index is the Dow Jones Industrial Average index.